GPRS telemetry system for high-efficiency electric competition vehicles - Gago-Calderón, Alfonso; Galbeño-Ruiz, Germán; Gago-Bohórquez, Alfonso Carlos (My University, 2013)
It has been generated a complete wireless electronic telemetry system for experimental electric competition vehicles. Its purpose is to optimize the processes of monitoring, analysis and evaluation of this type of vehicles designed by multidisciplinary groups of engineers, scientists, professors and students belonging to universities or research centers. Participation in competitions allows testing relevant developments and innovations in this technical field under severe real usage conditions and the system proposed offers a tool for real-time monitoring that is vital to optimize these processes during tests and races.
Keywords: Vehículos eléctricos; Project-based Education; Electric Racing Vehicles; Telemetry system; Wireless; GPRS